2019
DOI: 10.3390/ijms20020240
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Promoter Region of the MC4R Gene Elucidates the Association of Body Measurement Traits in Hu Sheep

Abstract: The melanocortin 4 receptor (MC4R) gene is expressed in the appetite-regulating areas of the brain and is engaged in the leptin signaling pathway. Although previous studies have identified variants in the coding region of the sheep MC4R gene showing significant associations with birth weight, weaning weight, and backfat thickness, no such associations have been reported for the promoter region. Besides, the essential promoter region of the sheep MC4R has not been delineated. In this study, to better understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It is located 187k bp from MC4R in a sequence that is not conserved in mice. Using TRANSFAC 110 , PROMO 111 , and JASPAR 112 , analysis of the risk allele found it to potentially disrupt binding of GATA binding protein 1 (GATA1), which was shown to bind to the 5’UTR of the MC4R gene 113 ( Fig.5d ). To characterize its function and test whether it regulates MC4R , we set out to knockout this sequence in neurons using CRISPR-Cas9.…”
Section: Resultsmentioning
confidence: 99%
“…It is located 187k bp from MC4R in a sequence that is not conserved in mice. Using TRANSFAC 110 , PROMO 111 , and JASPAR 112 , analysis of the risk allele found it to potentially disrupt binding of GATA binding protein 1 (GATA1), which was shown to bind to the 5’UTR of the MC4R gene 113 ( Fig.5d ). To characterize its function and test whether it regulates MC4R , we set out to knockout this sequence in neurons using CRISPR-Cas9.…”
Section: Resultsmentioning
confidence: 99%
“…Body measurement traits (BMTs), vitally responsible for body growth and economically important for breeding and production, have not yet been considered, although they are classical quantitative traits that have attracted the attention of geneticists for more than a century (Galton, 1886;Lund et al, 1994;Pryce et al, 2011;Wu et al, 2013). BMTs have been studied in pigs (Song et al, 2019;Zhou et al, 2019), cattle (Jin et al, 2018), and sheep (Shishay et al, 2019). In chickens, BMTs mainly include body slope length (BL), keel length (KL), chest width (CW), chest depth (CD), tibia length (TL), and tibia diameter (TD).…”
Section: Introductionmentioning
confidence: 99%
“…Among these loci, the melanocortin‐4 receptor ( MC4R ) gene plays an important role in the regulation of body weight, energy balance and reproduction in humans and animals (Bakos et al., 2016; Siljee et al., 2013; Zeng et al., 2014). The ovine MC4R gene is mapped on chromosome 23 and consists of two exons (Shishay et al., 2019). The MC4R gene is involved in the regulation of phenotype expressions of several economic traits in ruminant and non‐ruminant animals.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the MC4R gene variation have been recently implicated in the rapid growth selection program of beef cattle (Prihandini & Maharani, 2019). On the other hand, it has been shown that some of the variations detected in the MC4R gene have been associated with economic traits in livestock (Shishay et al., 2019). It has been recently reported that the MC4R gene polymorphism has exhibited a noticeable association with weight, body length and chest circumference gains, in addition to the average daily gain in goats (Latifah et al., 2018).…”
Section: Introductionmentioning
confidence: 99%